The Influence of Good Corporate Governance on Firm Performance (A Study in PT. Bank XYZ Indonesia Tbk.) - Andika, Zidni Fahra (Jurnal Ilmiah Mahasiswa FEB, 2018)
This  study  aims  to  determine  the  effect  of  good  corporate  governance  on  firm performance. This explanatory research, explains causal relationship between the variables through hypothesis testing, using quantitative approach. Using simple random sampling, 113  employees  are  selected  as  the  sample.  This  study  uses  multiple  linear  regression analysis.  The  result  shows  that  GCG  influences  firm  performance.  In  addition, transparency,  accountability,  responsibility,  independency,  and  fairness  partially  give  a significant effect on firm performance. Furthermore, the Adjusted R Squared value shows that the contribution of GCG on firm performance is 77,6% KEYWORDS: Good Corporate Governance, Firm Performance.